EFEKTIVITAS PENYULUHAN PERTANIAN TERHADAP KEBERHASILAN PROGRAM ASURANSI USAHA TANI TANAMAN PADI DI KABUPATEN LUMAJANG (The Effectiveness Of Agricultural Extension On The Success Of The Rice Farming Business Insurance Program In Lumajang District) - ADI, SUKARNO MUKTI; ARVIANTI, ERI YUSNITA; SANTOSO, BUDI (Universitas Mulawarman (University of Mulawarman), 2025)
This study examines the impact of agricultural extension on farmers' success in the Rice Farming Business Insurance Program (AUTP) in Lumajang Regency using the SEM-PLS method with a sample of 300 farmers from 14 sub-districts.The results show that all aspects of the extension worker's roles (facilitator, innovator, motivator, dynamist, and educator) have a significantly positive impact on the success of the AUTP, with the motivator role being the most dominant.Several constraints were identified, such as low participation, complicated claim processes, limited monitoring, and difficult access to services, thus recommending improvements in education, claim assistance, regular evaluations, and better access to information.In conclusion, the effectiveness of the AUTP program highly depends on the optimization of the role of extension workers, which can be enhanced through continuous training, effective communication, individual approaches, institutional support, and active farmer engagement.